The Flavonoid Biosynthesis Network in Plants - Liu, Weixin; Feng, Yi; Yu, Suhang; Fan, Zhengqi; Li, Xinlei; Li, Jiyuan; Yin, Hengfu (International journal of molecular sciences, 2021)
Flavonoids are an important class of secondary metabolites widely found in plants, contributing to plant growth and development and having prominent applications in food and medicine. The biosynthesis of flavonoids has long been the focus of intense research in plant biology. Flavonoids are derived from the phenylpropanoid metabolic pathway, and have a basic structure that comprises a C15 benzene ring structure of C6-C3-C6. Over recent decades, a considerable number of studies have been directed at elucidating the mechanisms involved in flavonoid biosynthesis in plants. In this review, we systematically summarize the flavonoid biosynthetic pathway. We further assemble an exhaustive map of flavonoid biosynthesis in plants comprising eight branches (stilbene, aurone, flavone, isoflavone, flavonol, phlobaphene, proanthocyanidin, and anthocyanin biosynthesis) and four important intermediate metabolites (chalcone, flavanone, dihydroflavonol, and leucoanthocyanidin). This review affords a comprehensive overview of the current knowledge regarding flavonoid biosynthesis, and provides the theoretical basis for further elucidating the pathways involved in the biosynthesis of flavonoids, which will aid in better understanding their functions and potential uses.